2023
DOI: 10.3390/microorganisms11020470
|View full text |Cite
|
Sign up to set email alerts
|

Local and Systemic Effects of Porphyromonas gingivalis Infection

Abstract: Porphyromonas gingivalis, a gram-negative anaerobe, is a leading etiological agent in periodontitis. This infectious pathogen can induce a dysbiotic, proinflammatory state within the oral cavity by disrupting commensal interactions between the host and oral microbiota. It is advantageous for P. gingivalis to avoid complete host immunosuppression, as inflammation-induced tissue damage provides essential nutrients necessary for robust bacterial proliferation. In this context, P. gingivalis can gain access to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 272 publications
(337 reference statements)
0
8
0
Order By: Relevance
“…E-cadherin and the BM are substrates for host proteases (like MMPs) and bacterial proteases, and the following disintegration of epithelial cell–cell connections and the BM enables bacterial invasion into the underlying tissue, initiating and preserving inflammation. The initiation of periodontal disease is attributed to cleavage within the second or third cell layer directly attached to tooth cells in the coronal-most portion of the JE facing biofilms [ 251 , 252 ]. Following cleavage, the secretion of cytokines and chemokines causes the accumulation of PMNs in the JE, which results in disruption of the epithelium by neutrophil proteases (e.g., cathepsin G, neutrophil elastase, and MMPs) [ 251 ].…”
Section: The Extracellular Matrix Of the Periodontium And The Role Of...mentioning
confidence: 99%
“…E-cadherin and the BM are substrates for host proteases (like MMPs) and bacterial proteases, and the following disintegration of epithelial cell–cell connections and the BM enables bacterial invasion into the underlying tissue, initiating and preserving inflammation. The initiation of periodontal disease is attributed to cleavage within the second or third cell layer directly attached to tooth cells in the coronal-most portion of the JE facing biofilms [ 251 , 252 ]. Following cleavage, the secretion of cytokines and chemokines causes the accumulation of PMNs in the JE, which results in disruption of the epithelium by neutrophil proteases (e.g., cathepsin G, neutrophil elastase, and MMPs) [ 251 ].…”
Section: The Extracellular Matrix Of the Periodontium And The Role Of...mentioning
confidence: 99%
“…In addition, it has been reported that oral bacteria sometimes cause bacteremia by tooth extraction or periodontitis, affecting various systemic diseases, such as endocarditis, diabetes, arteriosclerosis, and so on. [8][9][10] Hence, ARB in the oral cavity may also be a cause of bacteremia. Therefore, we need to pay more attention to ARB in the oral cavity not only for infection control but also for prevention of systemic disease.…”
Section: Introductionmentioning
confidence: 99%
“…ARB in the oral cavity are considered to spread the infection to other sites in individuals and to others through conversing, coughing, and eating. In addition, it has been reported that oral bacteria sometimes cause bacteremia by tooth extraction or periodontitis, affecting various systemic diseases, such as endocarditis, diabetes, arteriosclerosis, and so on 8–10 . Hence, ARB in the oral cavity may also be a cause of bacteremia.…”
Section: Introductionmentioning
confidence: 99%
“…A powerful periodontal bacteria called P. gingivalis can enter the bloodstream and cause a prothrombotic condition. P. gingivalis expresses a large number of virulence factors that help the organism to infect a range of host systems and cells, avoid spotting by the host immune system, trick the host immune system into producing the wrong antibodies, and activate several humoral and cellular hemostatic mechanisms [ 8 ].…”
Section: Introductionmentioning
confidence: 99%